Complexities of Theologies of Wealth and Prosperity: Africa in Focus - Eale, Bosela E.; Njoroge, J. Ngige (Regnum Books, 2022)
This volume addresses the theologies of Wealth and Prosperity putting the African Church in focus. Wealth and prosperity have become a subject of much wider interest in the Church at all level. The volume responds to the emergence of prosperity Gospel practices in both mission and African Independent Churches today. The book gives biblical perspectives on Wealth and Prosperity drawn from the Old and the New Testament. Preaching and teaching on wealth and prosperity have always been framed negatively. Discussions in this volume have explored ways wealth and prosperity can be framed positively, given the fact that God has endowed enormous and abundant resources in Africa
free